Boosting Proton Conductivity in Highly Robust 3D Inorganic Cationic Extended Frameworks through Ion Exchange with Dihydrogen Phosphate Anions. Issue 49 (22nd October 2015) - Xiao, Chengliang; Wang, Yaxing; Chen, Lanhua; Yin, Xuemiao; Shu, Jie; Sheng, Daopeng; Chai, Zhifang; Albrecht‐Schmitt, Thomas E.; Wang, Shuao
Abstract: The limited long‐term hydrolytic stability of rapidly emerging 3D‐extended framework materials (MOFs, COFs, MOPs, etc.) is still one of major barriers for their practical applications as new solid‐state electrolytes in fuel cells. To obtain hydrolytically stable materials, two H2 PO4 − ‐exchanged 3D inorganic cationic extended frameworks (CEFs) were successfully prepared by a facile anion‐exchange method. Both anion‐exchanged CEFs (YbO(OH)P and NDTBP) show significantly enhanced proton conductivity when compared with the original materials (YbO(OH)Cl and NDTB) with an increase of up to four orders‐of‐magnitude, reaching 2.36×10 −3 and 1.96×10 −2 S cm −1 at 98 % RH and 85 °C for YbO(OH)P and NDTBP, respectively. These values are comparable to the most efficient proton‐conducting MOFs. In addition, these two anion‐exchanged materials are stable in boiling water, which originates from the strong electrostatic interaction between the H2 PO4 − anion and the cationic host framework, showing a clear advance over all the acid‐impregnated materials (H2 SO4 @MIL‐101, H3 PO4 @MIL‐101, and H3 PO4 @Tp‐Azo) as practical solid‐state fuel‐cell electrolytes. This work offers a new general and efficient approach to functionalize 3D‐extended frameworks through an anion‐exchange process and achieves water‐stability with ultra‐high proton conductivity above 10 −2 S cm −1 . Abstract : Boosting and no leaching : Two stable H2 PO4 − ‐exchanged 3D inorganic cationic extended frameworks (CEFs) were prepared by a facile anion‐exchange method (see figure). Both anion‐exchanged CEFs show significantly enhanced proton conductivity with an increase of up to four orders‐of‐magnitude, reaching 2.36×10 −3 and 1.96×10 −2 S cm −1 at 98 % RH and 85 °C for YbO(OH)P and NDTBP, respectively.